Efektivitas Stencil Print dalam Mengembangkan Kemampuan Motorik Halus Anak Usia 5-6 Tahun di Taman Kanak-kanak Mekar Bunga Padang - Yulia Pratiwi, Putri; Yeni, Indra (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research was conducted with the aim of finding out how effective the use of stencil print media is in developing children's fine motor skills at Mekar Bunga Kindergarten, Padang. This type of research is a quantitative research with quasi-experimental methods. Data collection techniques in the form of tests, observations, and documentation. The population in this study were all students of Mekar Bunga Kindergarten, Padang, totaling 43 children. While the sample consisted of 20 children, 10 children in class B1 and 10 children in class B2. Data analysis used is hypothesis testing, T test, and effect size test. The results of the study showed that there was an effectiveness of using stencil print media on the development of children's fine motor skills with an initial score (pre-test) of 21.80 and a final score (post-test) of 26.80. Then from the calculation of the hypothesis test shows a significant level of 0.001. The results of the study using the effect size test obtained a value of 1.60 which is included in the strong category. Thus stencil print media with plastic cup media is effective in developing children's fine motor skills at Mekar Bunga Padang Kindergarten.